2007
DOI: 10.1007/s11243-006-0143-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Raman, FT-IR, EPR spectra and antimicrobial activity of 2-(5-H/Me/Cl-1H-benzimidazol-2-yl)-phenol ligands and their Fe(NO3)3 complexes

Abstract: 2-(5-H/Me/Cl-1H-benzimidazol-2-yl)-phenol ligands form 1:1 electrolytes, 5-coordinate monometallic complexes with iron(III) nitrate. The geometry of the [Fe(L)(OH)(H 2 O) 2 ](NO 3 ) complexes was derived from theoretical calculation in DGauss/DFT level (DZVP basis set) on CACHE. In all of the complexes the ligands are bidentate, via one imine nitrogen atom and phenolate oxygen atom. The coordination is completed with a hydroxide ion, and two water molecules, adopting a distorted square pyramidal geometry. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…3300 cm −1 in the IR spectra, caused by intramolecular hydrogen bonding between the phenoxyl hydrogen atom and C N nitrogen atom ( Table 2 and Fig. 2) [15,[28][29][30].…”
Section: Ir Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…3300 cm −1 in the IR spectra, caused by intramolecular hydrogen bonding between the phenoxyl hydrogen atom and C N nitrogen atom ( Table 2 and Fig. 2) [15,[28][29][30].…”
Section: Ir Spectramentioning
confidence: 99%
“…The other important benzimidazol derivatives, which are used as drugs, are thiabendazole [4,5], albendazole, mebendazole, flubendazole [6,7] astemizole [8] and fenbendazole [9]. In our previous studies, we found that various benzimidazolyl-phenol derivatives showed antimicrobial activity against several microorganisms [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…According to the molar conductivity data, [32][33][34]. The room temperature magnetic moment value of Co(II) complex, 3.31 BM, lower than the spin-only value for high spin and higher than the spin-only value for low spin configurations.…”
Section: Properties Of the Complexesmentioning
confidence: 99%
“…The high therapeutic properties of the related drugs have encouraged the medicinal chemists to synthesize a large number of novel chemotherapeutic agents [10][11][12]. They displayed many biological activities, such as: antiviral [13] and antitumoral [14]; antifungal and antimycotic [15]; antihistaminic and antiallergic [16]; antimicrobial [17][18][19][20] and antihelminthic activity [21]; all are unique characteristics known for benzimidazole derivatives [10]. These compounds are also extensively used in industrial processes as corrosion inhibitors for metal and alloy surfaces [22,23].…”
Section: Introductionmentioning
confidence: 99%